The social project : housing postwar France - Cupers, Kenny (University of Minnesota Press, 2014)
This study demonstrates how several bodies of knowledge - architectural, sociological, technological, and bureaucratic - shaped postwar modernism and the making of contemporary urban France. In less than three decades after WWII, France evolved from a largely rural country with an insufficient and outdated housing stock to a highly modernised urban nation. The book traces how this evolution resulted from an unprecedented upshift in production, ranging from mass housing and community centres to entirely new towns.